Characterization and antimicrobial analysis of cassava starch- chitosan blend biodegradable film with addition of black cumin oil - Nabilah, Omor (2010)
Biodegradable film made from renewable and naturals polymers such as starch had been in considerable interest. In addition to their undisputed advantage of being obtain from renewable resources, they are required to be biodegradable. In this study chitosan and starch are used as polymer. Chitosan has been found to be nontoxic, biodegradable, biofunctional and biocompatible in addition. Gelatin and polyethylene glycol (PEG) are use as additive to enhance the physical and chemical properties of the biodegradable film. The film preparation process consist of preparation of solution containing chitosan, starch, acetic acid, gelatin , PEG and black cumin oil as materials.. The solution was poured on a glass plate and left at ambient temperature until it completely dry. The film was then peeled off the glass plate. The fabrication films were characterized using fourier transform infrared spectroscopy (FTIR) , differential scanning calorimetry (DSC) , thermogravimetric analysis (TGA) , scanning electron microscope (SEM) and antimicrobial analysis using agar diffusion method (zone inhibition assay) and liquid culture test (optical density measurements). From the experiment result, the film containing of starch, gelatin and black cumin oil have higher thermal stability, compact matrix, slightly higher melting point and also greater antimicrobial properties. Thus, the film may have potential to be use for packaging by having good chemical , and physical properties and also inhibit bacterial growth.